Type synthesis of deployable single-loop overconstrained linkages based on Bennett linkages. (February 2018) - Guo, Hongwei; Song, Xiaoke; Li, Lifang; Deng, Zongquan; Liu, Rongqiang; Geng, Jinsong
Highlights: A series of spatial single-loop overconstrained linkages (SLOLs) is synthesized using Bennett linkages as the basic units. A set of single-loop kinematic chains is constructed by combining Bennett linkages, and their mobility is analyzed using screw theory. Linkages with zero joint offset are constructed based on the synthesized mechanisms. The deployability of the symmetric SLOLs and their relationship with Bricard linkages are investigated. Linkages with symmetric configurations are generated. Abstract: In this study, a series of spatial single-loop overconstrained linkages (SLOLs) is synthesized using Bennett linkages as the basic units. A set of 5R and 6R single-loop kinematic chains is constructed by combining Bennett linkages. The motion screw equations of these kinematic chains are obtained. Using screw theory their mobility is analyzed. Linkages with zero joint offset are constructed to create mechanisms with excellent deployability. The deployability of the SLOLs with symmetric configurations and their relationship with Bricard linkages are investigated. The symmetry of the obtained linkages is evaluated, and several linkages with line symmetry and plane symmetry are generated. Results show that a part of the synthesized linkages has excellent deployability and can serve as the units of deployable mechanisms. Intersections exist between the Bennett-based SLOLs and Bricard linkages.